Nuclear Astrophysics with the Trojan Horse Method. Issue 1 (January 2016) - Tumino, A; Spitaleri, C; Lamia, L; Pizzone, R G; Cherubini, S; Gulino, M; La Cognata, M; Puglia, S M R; Rapisarda, G G; Romano, S; Sergi, M L; Spartá, R
Abstract: The Trojan Horse Method (THM) represents the indirect path to determine the bare nucleus astrophysical S(E) factor for reactions between charged particles at astrophysical energies. This is done by measuring the quasi free cross section of a suitable three body process. The basic features of the THM will be presented together with some applications to demonstrate its practical use.